Aspects of Language - Bolinger Dwight (Harcourt, Brace & World, Inc, 1968)
Foreword, Born to Speak, Some Traits of Language, The Phonetic Elements, Structure in Language: The Units of Sound, Structure in Language: The Higher Levels, The Evolution of Language: Courses and Forces and Sounds and Spellings, The Evolution of Language: Meanings and Interpretations and Adjustments, The Evolution of Language: Views and Measurements, Dialect, Writing, The Evolving Approaches to Language, Mind in the Grip of Language, Some Practical Matters, Index.